Extraneous fibre traces brought by river water — A case study. Issue 1 (January 2017) - Lepot, L.; Vanden Driessche, T.; Lunstroot, K.; Barret, A.; Gason, F.; De Wael, K.
Abstract: The fibre traces on a young victim found underwater were mostly single fibre traces besides small amounts of fibre collectives indistinguishable from his parents clothes (mainly wool). Most of those single fibre traces were blue-grey polyester fibres showing tiny differences among each other. They were unexpected according to known population fibre studies. One year after the victim's discovery experiments were conducted to evaluate the possible contamination with fibres from river water. A small amount of extraneous fibres were collected among which blue and grey-black cotton and man-made (mainly polyester) fibres. All man-made fibres were single fibre traces and small fibre collectives were only observed for cotton. These results confirmed the frequent occurrence of blue and grey-black cotton fibres as background, but also highlighted the possible contamination with single blue and grey-black man-made fibres from river water. No wool was found, strengthening the significance of the wool fibre collectives present on the victim.